The Differential Impact of Knowledge Depth and Knowledge Breadth on Creativity over Individual Careers - Mannucci, Pier Vittorio; Yong, Kevyn (Academy of Management Journal, 2018)
While usually argued to be fostering creativity, the effect of knowledge depth and breadth on creativity is actually mixed. We take a dynamic approach to the knowledge–creativity relationship and argue that the effect of knowledge depth and knowledge breadth is likely to be contingent on career age. We propose that individuals’ knowledge structures become increasingly rigid as career age grows and that, because of this, knowledge depth and breadth have different effects on creativity at different points of the career. More specifically, we hypothesize that knowledge depth is more beneficial for creativity in earlier stages of one’s career, when creators need to increase the complexity of knowledge structures, while knowledge breadth is more beneficial in later stages, when flexibility is most needed. We test and find support for our hypotheses in a longitudinal study set in the context of the Hollywood animation industry, a setting characterized by the presence of a variety of creators involved in knowledge-intensive activities. Theoretical and practical implications of the results are discussed.